Kinetics of Oxidation Toluidines by Chromic Acid - Singh, Ranveer; Mishra, S.K. (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of o, m and p-toluidines by chromicacid has been studied in acetic acid-water medium. The reactionswere found to be fIrst order with respect to [Oxidant], [Substrate]and [H+]. An addition of Cu2+ and Ag + increases the rate of reactionwhile addition of Mn2+ decreases the rate of reaction in each case.An addition of neutral salts like NaCl, KCl, Na2SO4 and K2SO4 inthe reaction mixture showed negligible effect. Effects of dielectricconstant and temperature on the reactions were studied. Thermodynamicparameters have been evaluated and mechanism for thereactions have been proposed. The isokinetic temperature has alsobeen evaluated.